A Role for Sigma Factor σE in Corynebacterium pseudotuberculosis Resistance to Nitric Oxide/Peroxide Stress - Pacheco, Luis G.; Castro, Thiago L.; Carvalho, Rodrigo D.; Moraes, Pablo M.; Dorella, Fernanda A.; Carvalho, Natalia B.; Slade, Susan E.; Scrivens, James H.; Feelisch, Martin; Meyer, Roberto; Miyoshi, Anderson; Oliveira, Sergio C.; et al. (Frontiers in Microbiology, 2012)
Pathogenic intracellular bacteria can respond to antimicrobial mechanisms of the host cell through transient activation of stress-responsive genes by alternative sigma (σ) factors of the RNA polymerase. We evaluated the contribution of the extracytoplasmic function sigma factor σE for Corynebacterium pseudotuberculosis resistance to stress conditions resembling those found intracellularly during infection. A sigE null mutant strain (delta-sigE) of this bacterium was more susceptible in vitro to acidic pH, cell surface stressors, and biologically relevant concentrations of nitric oxide (NO). The same mutant strain was unable to persist in C57BL/6 mice but remained infective in mice lacking inducible nitric oxide synthase (iNOS), confirming the significance of σE for resistance to nitric oxide/peroxide stress in vivo. High-throughput proteomic analysis identified NO-responsive extracellular proteins of C. pseudotuberculosis and demonstrated the participation of σE in composition of this bacterium´s exoproteome.